Regional patterns and determinants of new firm formation and survival in Western Germany - Udo Brixy; Reinhold Grotz (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2006)
There is a large body of literature on the determinants of regional variation in new firm formation. In contrast there are few articles on the spatial differences in new firm survival. Using panel data we analyse both items for 74 western German regions over a ten-year period. The positive relationship between entry and exit which is often stated suggests a negative correlation between entry and survival. On the other hand, however, it seems convincing that regions with high birth rates should also have high survival rates, because a favourable environment for the founding of new firms should also be encouraging for the development of these firms. However, an analysis of both rates for 74 western German regions over a ten-year period reveals the existence of a negative relationship in general. This means that the survival rates are below average in regions with high birth rates. Despite this overall correlation, however, it is shown that the spatial pattern of a combination of both rates is complex, and all types of possible relationships exist. With a multivariate panel analysis we study the factors that influence regional birth and survival rates using the same set of independent variables. It is shown that in the service sector most variables literally work in opposite directions in the birth and survival rates models. But this does not hold for the manufacturing sector. This can be rated as evidence for the 'supportive environment thesis'. The reason for this is a completely different outcome of the estimated birth rates models for both industry sectors, whereas there are only minor differences in the estimated survival rate models. We can therefore deduce firstly that the two industries have different requirements for their 'seed bed' but not for their further successful development; and secondly, that the spatial structures which increase the number of newly founded businesses in the service sector are detrimental to the survival rates of newly founded firms.
Keywords: R11; J23; L25; M13; 330; Unternehmensgründung; regionale Disparität; Unternehmenserfolg; Wirtschaftszweige; Westdeutschland; Bundesrepublik Deutschland; Räumliche Verteilung; Unternehmensgründung; Erfolgsfaktor; Deutschland